Development of pH-sensitive polymeric nanoparticles for targeted drug delivery to the ischemic heart - Marques, Gonçalo Alexandre da Conceição Duarte (2017)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2017